Korean Guidelines for the Appropriate Use of Cardiac CT - Kim, Young Jin (Korean J Radiol, 2015)
The development of cardiac CT has provided a non-invasive alternative to echocardiography, exercise electrocardiogram, and invasive angiography and cardiac CT continues to develop at an exponential speed even now. The appropriate use of cardiac CT may lead to improvements in the medical performances of physicians and can reduce medical costs which eventually contribute to better public health. However, until now, there has been no guideline regarding the appropriate use of cardiac CT in Korea. We intend to provide guidelines for the appropriate use of cardiac CT in heart diseases based on scientific data. The purpose of this guideline is to assist clinicians and other health professionals in the use of cardiac CT for diagnosis and treatment of heart diseases, especially in patients at high risk or suspected of heart disease.